Defect tolerance of friction stir welds in DH36 steel. (15th December 2015) - Stevenson, Ryan; Toumpis, Athanasios; Galloway, Alexander
Abstract: Friction stir welding of steel is in the early stages of development. The aim to commercialise this process creates a trade-off between welding time, cost and quality of the joint produced. Therefore, it becomes critical to analyse the lower quality bound of steel friction stir welds in conventional square edge butt welding configuration. Work has been undertaken to evaluate the microstructure and fatigue performance of 6 mm thick DH36 steel plates friction stir welded with sub-optimal process conditions, resulting in the development of embedded and surface breaking flaws. The defective weldments were characterised to understand the nature of the flaws and a programme of mechanical testing was undertaken (including fatigue assessment) to determine the relationship between the flaw geometry, location and weld quality. A number of characteristic flaws were identified and seen to interact with the samples' fatigue fracture mechanisms. Samples with wormholes at the weld root produced the lowest fatigue performance. Fracture from incomplete fusion paths at the retreating side of the welds' top surface was seen to correspond to the highest recorded fatigue lives. The work provides an insight into the complex nature of characteristic flaws in steel friction stir welds and their interaction with fatigue behaviour. Graphical abstract: Highlights: Ductile failure in PM during tensile testing did not indicate inherent flaws. Fatigue performance of FSW of DH36 was influenced by characteristic flaws. The highest fatigue results corresponded to fracture at incomplete fusion paths. Longitudinal fatigue tests fractured from top surface incomplete fusion paths Tensile residual stresses reduced longitudinal fatigue lives.